1991
DOI: 10.1093/jmedent/28.1.152
|View full text |Cite
|
Sign up to set email alerts
|

Chorionic Structure of the Egg of the Screwworm, Cochliomyia hominivorax (Diptera: Calliphoridae)

Abstract: The chorion of the Cochliomyia hominivorax (Coquerel) egg is described using observations from scanning and transmission electron microscopy and light microscopy. Included are the gross structure and surface characteristics of the chorion, the basic architecture and internal components of the chorion proper, the location and function of the hatch lines, and the functional morphology of the plastron region as a respiratory structure. In the regular hexagonal arrangement and form of individual structural units, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
3
14
1
Order By: Relevance
“…cuprina conforms to general ultrastructural patterns shown by SEM micrographs of blow fly species (Kitching 1976; Erzinclioglu 1989; Liu and Greenberg 1989; Peterson and Newman 1991; Greenberg and Singh 1995; Sukontason et al 2004b), by bearing the dorsal plastron, micropyle and polygonal pattern of chorionic sculpture. The relatively wide plastron and slight bifurcation of the plastron near the micropyle of L .…”
Section: Resultssupporting
confidence: 78%
“…cuprina conforms to general ultrastructural patterns shown by SEM micrographs of blow fly species (Kitching 1976; Erzinclioglu 1989; Liu and Greenberg 1989; Peterson and Newman 1991; Greenberg and Singh 1995; Sukontason et al 2004b), by bearing the dorsal plastron, micropyle and polygonal pattern of chorionic sculpture. The relatively wide plastron and slight bifurcation of the plastron near the micropyle of L .…”
Section: Resultssupporting
confidence: 78%
“…7) and external hexagonal chorionic sculpture (Fig. 5) observed in C. nigripes, agreed with that recorded in the C. hominivorax egg reported by Peterson and Newman (1991). The function of the C. nigripes eggshell must fulfill several significant proposes including protection of the developing embryo from the environment, and the ability of sperm entry and gas exchange (Margaritis 1985).…”
supporting
confidence: 85%
“…However, this study indicated that the most distinct feature of the C. nigripes eggs was the chorionic sculpture, which bore a markedly elevated boundary in hexagonal pattern. This is different to the indistinct boundary observed in many blowfly species, e.g., Chrysomya bezziana Villeneuve, C. varipes (Macquart), C. rufifacies (Macquart), C. albiceps (Wiedemann), C. megacephala (F.), C. saffranea (Bigot), C. chloropyga (Wiedemann), Cochliomyia hominivorax (Coquerel) and C. macellaria (F.) (Kitching 1976;Peterson and Newman 1991;Greenberg and Singh 1995). Kitching (1976) Figs.…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…Elzinga (1987) reported that the chorion, which was secreted from the ovarian wall following surrounding of the oocyte with yolk before its release into the oviduct, gives the characteristic species shape and covering of the egg. The structure of the chorion was previously used to differentiate between species of May fly (Peterson and Newman 1991) and blow fly (Sukontason et al 2004).…”
Section: Discussionmentioning
confidence: 99%